LEGAL REVIEW OF THE EFFECTIVENESS OF PROVIDING LEGAL AID BY ADVOCATES THROUGH DIGITAL MEDIA - Ismaidar; Syaharani, Nabilah; Nurdiana, Citra; Saputra, Defri Dwi; Haharap, Rizki Nanda Fauzi (JILPR Journal Indonesia Law and Policy Review, 2025)
Technological advances in Indonesia have driven transformations in various sectors, including in the provision of legal aid services by advocates. This study examines the effectiveness of providing legal aid through digital media from a legal perspective, focusing on the opportunities and challenges faced in its implementation. Through a normative legal approach, this study analyzes the legal framework governing the practice of digital legal aid, including the Advocates Law, the ITE Law, and the Advocate Code of Ethics. The results of the study indicate that providing legal aid through digital media can increase the accessibility of legal services, especially for people in remote areas. However, its implementation still faces various challenges, such as the absence of specific regulations, data security issues, and digital infrastructure gaps. Advocates who provide services online can be categorized as Electronic System Organizers who must comply with the provisions of the ITE Law, especially regarding data protection and electronic transaction security. This study concludes that comprehensive regulatory updates are needed to regulate the practice of digital legal aid, as well as improving digital infrastructure and literacy to ensure service effectiveness. Key recommendations include the preparation of technical guidelines for the provision of digital legal aid and strengthening data security systems to protect client interests.